#Brumadinho, a tragédia: uma análise de avaliatividade segundo o subsistema de atitude - (:unkn) unknown (Universidade Federal de Goiás, 2021)
This research is part of the Postgraduate Program in Language Studies (PPGEL), of the Federal University of Goiás - Regional Catalão (UFG) / Federal University of Catalão (UFCAT). It aims to investigate, by way of lexical-grammatical elements, through the Attitude subsystem within the Evaluative System (HALLIDAY and MARTIN, 2005), how users of the social network Twitter position themselves and express their opinions on the 1st anniversary of the rupture of the dam of Córrego do Feijão mine in Brumadinho - MG. Thus, analyzing the Attitude subsystem in the investigated tweets, this work aims to contribute to the studies in Applied Linguistics, as well as in the Systemic-Functional Linguistics presented by Halliday (1994), which starts from the argument that language is a system of choices and that, by these choices, the interaction of individuals is possible. This theory is divided into three metafunctions of language, namely: ideational, textual, and interpersonal, which are understood and describe the linguistic components of a sentence. In addition to the theory used for this investigation, the computer program WordSmith Tools 7.0 was used to identify and contextualize the lexical-grammatical elements of Attitude present in the corpus. The Assessment System enabled the recognition of the types of Attitude (affection, judgment, and appreciation) about the tragedy that occurred in Brumadinho - MG, in which the participants demonstrate feelings, judgments, and values when mentioning what happened in their timeline. Therefore, in qualitative analysis, it is possible to note that users' tweets evaluate the event by three macro-categories: a) Brumadinho and Vale and their directors; b) Brumadinho and the victims and c) Brumadinho: tragedy or crime? Through the results achieved and the theoretical-methodological references, this study understands the occurrence of negative polarity in the analyzed tweets, in which users expressed their opinions. Most of the type of impact reaction was found through the Evaluation System compared to the other subtypes.
#Brumadinho, the tragedy: an appraisal analysis according to the attitude subsystem
Keywords: Sistema de avaliatividade; Hashtags; Subsistema de atitude; LSF; Appraisal system; Hashtags; Attitude subsystem; LSF; LINGUISTICA, LETRAS E ARTES::LINGUISTICA::FISIOLOGIA DA LINGUAGEM